2017
DOI: 10.3847/2041-8213/834/2/l15
|View full text |Cite
|
Sign up to set email alerts
|

Mode Conversion of a Solar Extreme-ultraviolet Wave over a Coronal Cavity

Abstract: We report on observations of an extreme-ultraviolet (EUV) wave event in the Sun on 2011 January 13 by Solar Terrestrial Relations Observatory (STEREO ) and Solar Dynamics Observatory (SDO ) in quadrature. Both the trailing edge and the leading edge of the EUV wave front in the north direction are reliably traced, revealing generally compatible propagation velocities in both perspectives and a velocity ratio of about 1/3. When the wave front encounters a coronal cavity near the northern polar coronal hole, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…The close temporal relationship between the EUV wave and upward SWs is shown in time-space plots ( Fig.5(e)-(g) and (i)). It has also been confirmed that the fast-mode MHD wave could be partly trapped inside magnetic loops rooting at magnetic QSLs and formed stationary front/brightenings Chen et al 2016, Yuan et al 2016Zong & Dai 2017). On the other hand, the interaction between the shock and the streamer-like structure is shown by the sudden change of the radio spectrum (the yellow box in Fig.2(d)).…”
Section: Conclusion and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The close temporal relationship between the EUV wave and upward SWs is shown in time-space plots ( Fig.5(e)-(g) and (i)). It has also been confirmed that the fast-mode MHD wave could be partly trapped inside magnetic loops rooting at magnetic QSLs and formed stationary front/brightenings Chen et al 2016, Yuan et al 2016Zong & Dai 2017). On the other hand, the interaction between the shock and the streamer-like structure is shown by the sudden change of the radio spectrum (the yellow box in Fig.2(d)).…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…Stationary brightenings resulted from the compression or/and persistent heating in wave or non-wave mechanisms (Ofman & Thompson 2002;Attrill et al 2007;Delannée et al 2007). Recently, it is proposed that stationary brightenings are as a result of the wave conversion from fast-mode to slow-mode, after the EUV wave is partially trapped inside the closed magnetic loops Zong & Dai 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since the converted slowmode wave propagates along the closed magnetic loops, and cannot run across the nearly vertical magnetic field lines, it looks like a stationary front when seen from above. The limb event studied by Zong & Dai (2017) provided the first support for the mode-conversion model.…”
Section: Discussionmentioning
confidence: 87%
“…Despite the debate on the nature of slow component of EUV waves, it is widely accepted that the fast component of EUV waves, especially when faster than 500 km s −1 , is a fast-mode magnetoacoustic wave or shock wave Long et al 2017b). Their wave nature can be inferred by various observational features, such as reflection (e.g., Long et al 2008;Gopalswamy et al 2009;Shen & Liu 2012c;Li et al 2012;Olmedo et al 2012;Yang et al 2013), transmission (e.g., Liu et al 2012;Olmedo et al 2012;Shen et al 2013a), refraction (e.g., Shen & Liu 2012a;Shen et al 2013a), and mode conversion (e.g., Chen et al 2016;Zong & Dai 2017;Chandra et al 2018). In particular, Shen et al (2013a) observed many of these features in a single EUV wave event, which clearly demonstrated the wave nature of EUV waves.…”
Section: Introductionmentioning
confidence: 99%